Instilling Pancasila Student Profile Values in The Formation of Student’s Character in Civic Education Subjects - Indriani, Dina; Saleh, Syarbaini (Graduate Program Magister Manajemen Pendidikan, 2024)
This study aims to provide knowledge about the inculcation of Pancasila student profile values in the formation of student character. The type of research used is qualitative research with a descriptive method. This study has a uniqueness, namely that usually character formation is only through civic education subjects, but in this study character formation is carried out through the profile values of Pancasila students. The results of this study show that the inculcation of Pancasila student profile values in the formation of student character is carried out through divinity and piety programs, namely dhuha prayers, memorization of surah and yasinan, work harvest programs, and mutual cooperation. This study is important to provide knowledge of PKn teachers in instilling the values of the Pancasila student profile to form student character. Therefore, with this study, it is hoped that readers, especially civic education teachers, can instill the values of the Pancasila student profile to shape the character of students. Thus, the implication of this study is that the research supports curriculum renewal by including activities that integrate Pancasila values more deeply. The curriculum can be expanded with practical projects and hands-on experience to reinforce the internalization of those values.